The Covid-19 Pandemic and the Rights of the Individual in Terms of Private and Public Law - Kharytonov, Evgen; Kharytonova, Olena; Kolodin, Denis; Tkalych, Maxym (Ius Humani. Jornal do direito, 2020)
The principles of adjusting the regulation of civil relations in the context of the Covid-19 pandemic are analyzed. The admissibility of restricting human rights in the context of the conflict of private and public interests are researched. Besides, the authors tried to determine the optimal algorithm of government actions aimed at preventing the spread of the epidemic. The main approach to the understanding of human rights in the article is based on Dworkin's concept of " rights as trumps". A system of such categories as " a man", " a private person", " natural private rights", " private law" and " national civil law" is analyzed. The conclusion is that the importance of the category of " natural" human rights is underestimated, which exacerbates the problem of ensuring human rights in a pandemic, when the state actively uses public law to cope with the crisis. As a result, there is a conflict of basic principles of private and public law: " everything is allowed except what is prohibited by law" vs. " only what is allowed by law is possible". It is proposed to assume that the usual way of the legal existence of a person is that he/she acts as a participant in civil relations of a private type, even in a pandemic. Private relations, which arise during the quarantine period, are proposed to be regulated mainly by private law methods, limiting the influence of the state. This will allow us to reach a compromise of private and public interests, without restricting the rights of individuals voluntarily.